Utilización de tecnologías del lado del cliente para dotar de capacidades de personalización visual a una aplicación Front End que interactúe con Moodle - Olmedo Vilca, Paola Alexandra (2018)
Applying the knowledge acquired during the Systems Engineering Career, this project aims to allow the customization of a website (virtual classroom), demonstrating that it is more efficient to consume the technologies on the client side than on the server side. Should consider: insert a wallpaper on a website, change the color and shape of the components and change the location of them. It is going to prove that it is possible to make personalization of a website, and users can customize the site and browse freely with ease. To achieve these objectives: AngularJs as a framework, which allows working on the client's side, together with the Moodle e-learning platform as a content provider, together allowed the development of this project.